2018
DOI: 10.11648/j.ajls.20180605.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Acute Malnutrition Among 6-59 Month Children in Adi-Harush and Hitsats Refugee Camps in Tigray Region Northern Ethiopia, 2017

Abstract: Background: Wasting is characterized by low weight for height and it is common in developing countries. Wasted children have lower resistance to infection, impaired learning ability and reduce economic productivity. Objective: The aim of this study was to assess the prevalence and associated factors of acute malnutrition among children aged 6-59 months in Adiharush and Hitsats Eritrean refugee camps. Methods: A community-based cross-sectional study was conducted from March 1 to April 15/2017, at Adi-Harush and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…The finding of this study revealed that 14.7% of children were wasted. This finding is higher than the findings in 2019 Ethiopian Mini Demographic and Health survey result (7%) [ 10 ], Northwest Ethiopia (10%) [ 14 ] and Adi-Harush and Hitsats Refugee Camps in Tigray (11%) [ 15 ]. The difference might be due to the difference in the study period and the population participated in the study.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The finding of this study revealed that 14.7% of children were wasted. This finding is higher than the findings in 2019 Ethiopian Mini Demographic and Health survey result (7%) [ 10 ], Northwest Ethiopia (10%) [ 14 ] and Adi-Harush and Hitsats Refugee Camps in Tigray (11%) [ 15 ]. The difference might be due to the difference in the study period and the population participated in the study.…”
Section: Discussioncontrasting
confidence: 57%
“…In Ethiopia, the prevalence of wasting was 10% in EDHS, 2016 [ 4 ] and 7% in Ethiopia mini demographic and health survey (EMDHS) [ 10 ]. There was also the regional variations with the highest percentages of wasting in under-five children such as 21% in Somali, 14% in Afar, 13% in Gambella, 2% in Addis Ababa and 4% in Harari [ 10 ], 13.4% in Bulehora district [ 13 ], 10% in Northwest Ethiopia [ 14 ], 11% in Adi-Harush and Hitsats Refugee Camps in Tigray Region [ 15 ], 11.1% in Dilla town [ 16 ] and 28.2% in Hawassa Zuria district [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Box: 32, Tuluawlyia, Ethiopia. 2 Department of Rural Development and Agricultural Extension, Mekdela Amba University, P.O. Box: 32, Tuluawlyia, Ethiopia.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Malnutrition happens when there are insufficient amounts of nutrients and energy consumed improperly. Included are both undernutrition and overnutrition [1,2]. Under-five children who are malnourished experience nutritional deficits as a result of the interaction between illness and poor nutrition [3,4].…”
Section: Introductionmentioning
confidence: 99%